A new record of species Asarum cordifolium C. E. C. Fischer (Aristolochiaceae) for the flora of Vietnam - Tuan, Nguyen Anh; Thai, Tran Huy; Wang, Jenn-Che; Lu, Chang-Tse (Academia Journal of Biology, 2012)
The genus Asarum L. comprised about 90 species, mainly distributed in East Asia (Chinna, Japan and Vietnam), North America and European. There were 7 species of Asarum recorded in Vietnam. This paper reported the species Asarum cordifolium C. E. C. Fischer  newly recorded for the flora of Vietnam. Asarum cordifolium C. E. C. Fischer: Herbs, rhizomes horizontal, height 15-25 cm, internodes 2-3 cm. Leaves solitary, 1-4; orbicular, 7-8 × 8-12 cm; leaf edges entire, villous; leaf blade densely white pubescents; petiole 12-20 cm, viollus; lateral veins 5. Single flower, red, white pubescents; peduncle 2 cm, densly white bubencents. Cataphylls lanceolate. Sepals free; lobes red, 1.2 × 2.0 cm; apex abuptly narrowed to a slender cauda 1-1.5 cm. Petals 3, needle, red, 0.3 cm. Stamens 12, filament as long as anthers, red-purple; connectives extended beyond anthers, tongue. Styles 6-connate, as long as anthers; apex entire. Ovary middle. Fl. Oct-Nov. Dense forest, moist valleys; 1.500-1.600 m. Sa Pa (Lao Cai province), Assam (India) and N Myanmar